Salivary decorin as a potential noninvasive biomarker in chronic kidney disease: a comparative study with serum levels - Karatutlu, Asena Serap; Karatutlu, Mehmet Ali; Aydin, Suleyman (Taylor & Francis Ltd, 2026)
Chronic kidney disease (CKD) is characterized by progressive renal fibrosis and irreversible loss of kidney function. Decorin, an extracellular matrix proteoglycan with antifibrotic properties, may reflect underlying fibrotic activity and has emerged as a potential biomarker. However, its role in noninvasive biological fluids such as saliva remains unclear. In this cross-sectional study, 88 patients with CKD stages 3-5 and 30 healthy controls were included. Serum and unstimulated saliva samples were collected simultaneously, and decorin levels were measured using enzyme-linked immunosorbent assay (ELISA). Group comparisons were performed using non-parametric tests, and correlations were analyzed using Spearman's method. Serum decorin levels showed an increasing trend with advancing CKD stage; however, these differences did not reach statistical significance and were not correlated with renal function parameters. In contrast, salivary decorin levels were significantly lower in CKD patients compared to controls and demonstrated a numerical decrease across CKD stages. No significant correlation was observed between serum and salivary decorin levels. Salivary decorin may represent a potential noninvasive candidate marker in CKD; however, further large-scale longitudinal studies are required to validate these findings.
Keywords: Chronic Kidney Disease; Decorin; Saliva; Biomarker; Fibrosis